(untitled) (European Journal of Pure and Applied Mathematics, 2024)
The influx of researches on hyperstructure theory has encouraged many researchers to introduce new algebras. Notable among these is the work of Indangan and Petalcorin who introduced hyper GR-algebra and that of Macodi and Petalcorin who studied fuzzification of hyper GR-algebra. Macodi extended the fuzzification of hyper GR-algebra into intuitionistic fuzzification and introduced the concept of an intuitionistic fuzzy hyper GR-ideal. Following the works of Macodi and Petalcorin, this paper established an intuitionistic fuzzy implicative hyper GR-ideal and obtained its characterization using level subsets. Moreover, some properties of intuitionistic fuzzy implicative hyper GR-ideals are presented.